HIV-1 Viral Subtype Differences in the Rate of CD4(+) T-Cell Decline Among HIV Seroincident Antiretroviral Naive Persons in Rakai District, Uganda - Kiwanuka, Noah (2010)
BACKGROUND: Data on the effect of HIV-1 viral subtype on CD4(+) T-cell decline are limited. METHODS: We assessed the rate of CD4(+) T-cell decline per year among 312 HIV seroincident persons infected with different HIV-1 subtypes. Rates of CD4(+) decline by HIV-1 subtype were determined by linear mixed effects models, using an unstructured convariance structure. RESULTS: A total of 59.6% had D, 15.7% A, 18.9% recombinant viruses (R), and 5.8% multiple subtypes (M). For all subtypes combined, the overall rate of CD4(+) T-cell decline was −34.5 [95% confidence interval (CI), −47.1, −22.0] cells/μL per yr, adjusted for age, sex, baseline CD4(+) counts, and viral load. Compared with subtype A, the adjusted rate of CD4 cell loss was −73.7/μL/yr (95% CI, −113.5, −33.8, P < 0.001) for subtype D, −43.2/μL/yr (95% CI, −90.2, 3.8, P = 0.072) for recombinants, and −63.9/μL/yr (95% CI, −132.3, 4.4, P = 0.067) for infection with multiple HIV subtypes. Square-root transformation of CD4(+) cell counts did not change the results. CONCLUSIONS: Infection with subtype D is associated with significantly faster rates of CD4(+) T-cell loss than subtype A. This may explain the more rapid disease progression for subtype D compared with subtype A.